Distinct Transcriptomic and Proteomic Profile Specifies Patients Who Have Heart Failure With Potential of Myocardial Recovery on Mechanical Unloading and Circulatory Support. Issue 5 (30th November 2022) - Drakos, Stavros G.; Badolia, Rachit; Makaju, Aman; Kyriakopoulos, Christos P.; Wever-Pinzon, Omar; Tracy, Christopher M.; Bakhtina, Anna; Bia, Ryan; Parnell, Timothy; Taleb, Iosif; Ramadurai, Dinesh K.A.; Navankasattusas, Sutip; et al.
Abstract : Background: Extensive evidence from single-center studies indicates that a subset of patients with chronic advanced heart failure (HF) undergoing left ventricular assist device (LVAD) support show significantly improved heart function and reverse structural remodeling (ie, termed "responders"). Furthermore, we recently published a multicenter prospective study, RESTAGE-HF (Remission from Stage D Heart Failure), demonstrating that LVAD support combined with standard HF medications induced remarkable cardiac structural and functional improvement, leading to high rates of LVAD weaning and excellent long-term outcomes. This intriguing phenomenon provides great translational and clinical promise, although the underlying molecular mechanisms driving this recovery are largely unknown. Methods: To identify changes in signaling pathways operative in the normal and failing human heart and to molecularly characterize patients who respond favorably to LVAD unloading, we performed global RNA sequencing and phosphopeptide profiling of left ventricular tissue from 93 patients with HF undergoing LVAD implantation (25 responders and 68 nonresponders) and 12 nonfailing donor hearts. Patients were prospectively monitored through echocardiography to characterize their myocardial structure and function and identify responders and nonresponders. Results: These analyses identified 1341 transcripts and 288 phosphopeptides that are differentially regulated in cardiac tissue from nonfailing control samples and patients with HF. In addition, these unbiased molecular profiles identified a unique signature of 29 transcripts and 93 phosphopeptides in patients with HF that distinguished responders after LVAD unloading. Further analyses of these macromolecules highlighted differential regulation in 2 key pathways: cell cycle regulation and extracellular matrix/focal adhesions. Conclusions: This is the first study to characterize changes in the nonfailing and failing human heart by integrating multiple -omics platforms to identify molecular indices defining patients capable of myocardial recovery. These findings may guide patient selection for advanced HF therapies and identify new HF therapeutic targets.